A conceptual framework for the development of educational games for children with dyscalculia (Research, Society and Development, 2025)
Dyscalculia is a specific learning disorder characterized by persistent difficulty in understanding numerical concepts, performing basic operations, and establishing mathematical relationships. Educational games can support children with this disorder by providing playful activities that stimulate essential cognitive skills. This study aims to propose the creation of a conceptual framework oriented toward the development of educational games (DEG – Dyscalculia Educational Games) for children with dyscalculia, offering clear guidelines for adapting pedagogical activities, selecting appropriate technologies, and structuring the development process in a manner consistent with users’ cognitive and educational needs. To validate its application, two educational games were developed: Aprendenúmeros  and Pronarrar. The results indicate that the DEG framework provides adequate support for aligning pedagogical, cognitive, and computational requirements, contributing to the development of more structured games that are coherent with the needs of the target audience.